Intermetallic Fe–Ti alloy obtained by dual-wire electron-beam additive manufacturing - Elena G. Astafurova; Lidiya V. Danilova; Aleksey S. Nifontov; Andrey V. Luchin; Sergey V. Astafurov; Evgeniy A. Kolubaev (Next Materials)
Fe–Ti intermetallic alloys are among the most perspective materials for hydrogen storage. Like many intermetallics, they are brittle and their quality, including hydrogen accumulation capacity, depends significantly on the composition and production method. Despite conventional casting and solid-state synthesis are commonly used for preparing Fe-Ti alloys, additive manufacturing can be assumed as alternative, fast and flexible production technique for intermetallic compounds. The range of mechanical properties and microstructures of Fe-Ti alloys by additive manufacturing is still inadequate, this limits their industrial application as materials for hydrogen storage. In this study, we successfully used a novel strategy for obtaining bulk poreless and crack-free billet of the Fe–Ti intermetallic alloy by a dual-wire electron-beam additive manufacturing using commercial wires of a Grade-2 titanium and low-carbon steel. Using X-ray analysis, scanning electron microscopy, and energy-dispersive X-ray spectroscopy, we have found that as-built material possesses dendritic microstructure: FeTi phase prevails in interdendrites and Fe2Ti intermetallic dominates in dendrites. In the central part of the billet, where the ratio of dendritic and interdendritic area is about 42 %/58 %, the alloy exhibits high yield strength (1230 MPa), ultimate compressive stress (1380 MPa) and 3 % engineering strain in compression. The presented results show that the electron-beam additive manufacturing is a promising method for the creation of bulk intermetallic materials of the Fe-Ti system that are important for hydrogen storage.